The 2007–2009 Financial Crisis: An Erosion of Ethics: A Case Study - Schoen, Edward J. (Journal of business ethics, 2017)
This case study examines five dimensions of the 2007–2009 financial crisis in the United States: (1) the devastating effects of the financial crisis on the U.S. economy, including unparalleled unemployment, massive declines in gross domestic product (GDP), and the prolonged mortgage foreclosure crisis; (2) the multiple causes of the financial crisis and panic, such as the housing and bond bubbles, excessive leverage, lax financial regulation, disgraceful banking practices, and abysmal rating agency performance; (3) the extraordinary efforts of the Federal Reserve, the Federal Reserve Bank of New York, and the Department of the Treasury to stem the financial freefall triggered by the crisis and resuscitate financial institutions, (4) the ethical implications of the unprecedented actions by government institutions to rescue financial institutions and drag the country back from the brink of global financial collapse, and the conduct of the various parties contributing to the financial crisis, such as the shoddy behavior of mortgage brokers, the massive securitization of mortgages into overly complex bonds, the excessive leverage of financial institutions, the disgraceful work of bond rating firms, the abysmal risk management systems employed by financial institutions, and the massive operations of the shadow banking and over-the-counter derivatives markets; and (5) the major provisions of the Dodd–Frank Wall Street Reform and Consumer Protection Act signed into law to in response to the financial crisis and for the purpose of correcting the egregious conduct of major financial institutions.